(untitled) (Journal of Dentistry and Allied Science, 2023)
Objective: The aim of the study was to find out the effect of Aqueous Emblica officinalis (amlaki) extract on Staphylococcus aureus and to detect the bacterial susceptibility to Aqueous Emblica officinalis (amlaki) extract and Gentamicin. Methods: Bacterial susceptibility of Aqueous Emblica officinalis (amlaki) extract on Staphylococcus aureus was determined by broth dilution method. Results: Aqueous amlaki extract has inhibitory effect on growth of S. aureus at 15.62 mg/5ml and in subsequent higher concentration. So the MICs value of AAE was 15.62 mg/5ml for S.aureus. S.aureus was sensitive against gentamicin at 10 μg disc potency with zone Diameter of inhibition more than 15mm. Zone Diameter of inhibition was 17.25±0.27 mm for S.aureus. Conclusions: The data suggest that the plant Emblica officinalis (amlaki) has antibacterial effect on S.aureus . There is potential possibility of developing this plant as a source of antimicrobial agent. Journal of Dentistry and Allied Science, Vol. 6 No 2: 25-29